Caracterização das gotículas respiráveis geradas por nebulizadores utilizando técnica de incidência laminar direta (ILD) - Araújo, Luciana Martins Pereira de (2019)
Pneumatic and ultrasonic nebulizers are increasingly used by children, the elderly, or the chronically ill, because of the ease with which these devices deliver the drugs through an aerosol suspension. The choice of nebulizers is related to the ability of these devices to perform the delivery of drugs in a localized way in the respiratory tract, providing a greater efficiency of absorption through the lung. The aim of the present work is to characterize the diameters of the micro droplets by bands of "breathable particles" generated by a sample of commercial nebulizers commercialized in the Brazilian market, using the technique of direct laminar incidence (ILD).Six (6) nebulizers of different marks were taken as samples, being 4 pneumatic and 2 ultrasonic. In the nebulization procedure the images of the dispersed aero micro droplets were captured through the ILD (Direct Laminar Incidence) technique consisting of a high-speed digital camera coupled to an inverted microscope and the captured images processed by software in an environment MATLAB® for the automated characterization of the diameter bands of the dispersed aero micro droplets generated in the nebulization process. Histograms of the micro droplet diameter distribution of the six nebulizers surveyed were developed emphasizing the range of breathable micro droplets, i.e., diameters ranging from 1.0-5.0 µm. The results attest that each nebulizer has its own characteristic of delivering the aerodynamic suspension in the nebulization process. This feature is closely related in their ability to generate micro droplets in the range classified as breathable. The results of the measurements point to another way of classifying nebulizers based on the criterion previously mentioned. Due to the haracteristics of each nebulizer in generating the aerodynamic cloud, it becomes plausible the future development of a more comprehensive evaluation protocol, based on the delivery of micro droplets in the ideal range, providing a better marking of the efficiency of the domestic nebulizers in the administration of drugs by inhalation.